A simulation method to find the optimal design of photovoltaic home system in Malaysia, case study: a building integrated photovoltaic in Putra Jaya - Muhida, Riza; Ali, Maisarah; Jahn Kassim, Puteri Shireen; Edy Sutjipto, Agus Geter; Abu Eusuf, Muhammad; Afzeri, Afzeri (World Academy of Science, Engineering and Technology (W A S E T), 2010)
Over recent years, the number of building integrated photovoltaic (BIPV) installations for home systems have been increasing in Malaysia. The paper concerns an analysis - as part of current Research and Development (R&D) efforts - to integrate photovoltaics as an architectural feature of a detached house in the new satellite township of Putrajaya, Malaysia. The analysis was undertaken using calculation and simulation tools to optimize performance of BIPV home system. In this study, a the simulation analysis was undertaken for selected bungalow units based on a long term recorded weather data for city of Kuala Lumpur. The simulation and calculation was done with consideration of a PV panels' tilt and direction, shading effect and economical considerations. A simulation of the performance of a grid connected BIPV house in Kuala Lumpur was undertaken. This case study uses a 60 PV modules with power output of 2.7 kW giving an average of PV electricity output is 255 kWh/month..